Pengaruh Model Pembelajaran Kooperatif Tipe Team Assisted Individualization terhadap Hasil Belajar Siswa - Odilia Juana Soares; Wolfgang Asindo Seran; Stefania Sonia Manek (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Effect of the Team Assisted Individualization Type Cooperative Learning Model to Improve Geography Student Learning Outcomes in Grade X Students of Bolan State Senior High School. The background of this study is based on in initial observations by researchers at Bolan State Senior High School on class X.A and X.B students, X.A Was used as an experimental group by implementing the team assisted invidualization.(TAI) coperatif learning model. The duration of this study, in a week in the form of 2x meetings for one month. The results of the study showed that there was an influence of the implementation of the cooperative learning model of the team assisted individualization (TAI) type on the learning outcomes of geography subjects of class X students of Bolan State Senior High School. Comprehensively, the results were (1) The learning outcomes of experimental class students in the initial test (pretest) showed that the average pre-test score on the Basic Knowledge of Geography material was 56.90 and the learning outcomes of experimental class students in the final test (posttest) showed that the average pre-test score on the Basic Knowledge of Geography material was 81.61. (2) The learning outcomes of the control class in the initial test (pretest) showed that the average pre-test score on the Basic Knowledge of Geography material was 51.24 while the learning outcomes of the control class in the final test (posttest) showed that the average pre-test score on the Basic Knowledge of Geography material was 72.72. Judging from the two trials, it showed that there was an increase in learning outcomes and the average score of the basic knowledge of geography material in the experimental class and the control class.